1996
DOI: 10.1016/s0022-5223(96)70043-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolated lung perfusion with platinum in the treatment of pulmonary metastases from soft tissue sarcomas

Abstract: A multimodality approach including operation and isolated lung perfusion with platinum was used in six patients with lung metastases from soft tissue sarcomas. Staged thoracotomies were used in two patients with bilateral lesions. The inclusion criteria generally applied for surgical excision were adopted in this study. The pulmonary artery and a portion of the left atrium were isolated from systemic circulation and cannulated. The cannulas were then connected to a perfusion circuit and normothermic isolated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1
9

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 26 publications
1
50
1
9
Order By: Relevance
“…First, isolated lung perfusion results in significantly higher drug concentrations in both lung and tumor tissue compared with i.v. administration as shown by many experimental and human data (Pass et al, 1996;Ratto et al, 1996;Hendriks et al, 1998Hendriks et al, , 2004Burt et al, 2000;van Putte et al, 2002). High-dose drug administration during isolated lung perfusion using drugs like gemcitabine and cisplatin is well tolerated by healthy lung tissue (Ratto et al, 1996;van Putte et al, 2003avan Putte et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, isolated lung perfusion results in significantly higher drug concentrations in both lung and tumor tissue compared with i.v. administration as shown by many experimental and human data (Pass et al, 1996;Ratto et al, 1996;Hendriks et al, 1998Hendriks et al, , 2004Burt et al, 2000;van Putte et al, 2002). High-dose drug administration during isolated lung perfusion using drugs like gemcitabine and cisplatin is well tolerated by healthy lung tissue (Ratto et al, 1996;van Putte et al, 2003avan Putte et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…administration as shown by many experimental and human data (Pass et al, 1996;Ratto et al, 1996;Hendriks et al, 1998Hendriks et al, , 2004Burt et al, 2000;van Putte et al, 2002). High-dose drug administration during isolated lung perfusion using drugs like gemcitabine and cisplatin is well tolerated by healthy lung tissue (Ratto et al, 1996;van Putte et al, 2003avan Putte et al, , 2005. Furthermore, a recent phase I trial evaluating toxicity of isolated lung perfusion with melphalan showed a rapid pulmonary lymph drainage resulting in equivalent concentrations in either the lymph nodes and lung tissue, although this approach is applied only once or twice per patient because of its invasive nature (unpublished data).…”
mentioning
confidence: 99%
“…Significantly higher lung tissue concentrations were obtained compared to systemic treatment or pulmonary artery blood flow occlusion (147,148). Kaneda et al (149) showed that ILuP with cisplatin was pharmacokinetically superior to IV treatment in a rodent model.…”
Section: Cisplatinmentioning
confidence: 99%
“…For instance, Johnston's group only included unresectable metastases whereas Ratto and Schröder investigated two different patient groups: resectable lung metastases and patients without any other treatment option left. Ratto used 3 times greater cisplatin concentration compared to Schröder without any additional histological damage (128,148,160). These variations make it very hard to draw any conclusions, especially on the reported survival data.…”
Section: Cisplatinmentioning
confidence: 99%
“…Isolated lung perfusion (ILP) has been explored in clinical and experimental settings for the management of lung metastasis and demonstrated efficient delivery of cytostatic agents to the perfused lung with excellent separation between systemic and pulmonary circulations [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. In an experimental model of sarcoma tumors grown on rodent lungs [10], doxorubicin ILP resulted in high drug uptake in the perfused lung with minimal systemic leakage and toxicity [11].…”
Section: Introductionmentioning
confidence: 99%